2013
DOI: 10.1080/15459624.2013.818236
|View full text |Cite
|
Sign up to set email alerts
|

Prevention Guidance for Isocyanate-Induced Asthma Using Occupational Surveillance Data

Abstract: Data from Washington State's work-related asthma surveillance system were used to characterize isocyanate-induced asthma cases occurring from 1999 through 2010. Injured worker interviews and medical records were used to describe the industry, job title, work process, workers’ compensation cost, and exposure trends associated with 27 cases of isocyanate-induced asthma. The majority (81%) of cases were classified within the surveillance system as new-onset asthma while 19% were classified as work-aggravated asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Of particular concern was the listing of polyurethanes as an ingredient in one of the nail polish brands found in the salons studied. Polyurethanes have been well documented as potent sensitizers in the autobody industry . This was particularly concerning, as the nail polish containing polyurethanes was labeled as non‐allergenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern was the listing of polyurethanes as an ingredient in one of the nail polish brands found in the salons studied. Polyurethanes have been well documented as potent sensitizers in the autobody industry . This was particularly concerning, as the nail polish containing polyurethanes was labeled as non‐allergenic.…”
Section: Discussionmentioning
confidence: 99%
“…Polyurethanes have been well documented as potent sensitizers in the autobody industry. 69 This was particularly concerning, as the nail polish containing polyurethanes was labeled as non-allergenic.…”
Section: Nail Salon Vocs and Nail Technician's Healthmentioning
confidence: 99%
“…More importantly, isocyanates may not be airborne at consistent levels during all work hours. Isocyanate use may be intermittent (e.g., spill cleanup), product‐specific, related to infrequent maintenance, or exposure may be indirect [Petsonk et al, ; Reeb‐Whitaker et al, ]. In addition, accurate air sampling for isocyanates is difficult, imprecise, and dependent on whether isocyanates are in gas or aerosol form, the size of the particles, the extraction and laboratory analysis methods used and the effectiveness in capturing monomers and polymers [Streicher et al, ; Bello et al, ; Lesage et al, ; Henneken et al, ; Booth et al, ; Thomasen et al, ; Reeb‐Whitaker et al, ; Schaeffer et al, ; Lockey et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar type of study, Washington State's work-related asthma surveillance system, was reported and has illustrated the exposure risk of workers to isocyanates when spraying foam insulation in buildings which characterized isocyanate-induced asthma cases. 58 For construction, MDI and TDI would be the major isocyanates used in majority of polyurethane products for buildings. Isocyanates could cause irritation to the skins and eyes, mucous membranes, and respiratory system.…”
Section: Good Practice Guide To Manage Risksmentioning
confidence: 99%